Investigating Grammar Learning Strategies Employed by Freshmen at University of Darussalam Gontor - Eka Indah Nuraini (International Journal of English Learning and Applied Linguistics (IJELAL), 2020)
This study explored types of grammar learning strategies (GLS) used by freshmen of University Darussalam Gontor and their ways in applying GSL in grammar class. This research employed survey research design by gathering data from questionnaire adapted from Bayou (2015) which was modified from Oxford (1990) Language Learning Strategies Classification and open-ended interview. As many as 35 of 60 students (58.3%) who consisted of males and females completed the questionnaire voluntarily. The data were analyzed in simple numerical statistics for the RQ1 and described in details for the RQ2. The result of the study revealed that compensation strategies were the most preferred strategy used by students as many as 75%. It meant that the students were more conscious in using the strategy of grammar knowledge. These results of percentage illustrated that the students employed direct strategies more than indirect strategies. Further, the ways students employed GLS in grammar classroom were described in details.